COMPETITION POLICY AND OPTIMAL RETAIL NETWORK DEVELOPMENT IN TRANSITIONAL ECONOMIES - Lovreta, Stipe; Milošević, Siniša; Stanković, Ljiljana (Economic Annals, 2013)
The choice of retail store location is a very complex process, with many different stakeholders having interests in both the micro and macro locations. The goal of this work is to contribute to the better understanding of the different interests of corporative and public policies in choosing retail store locations, in order to enable more efficient and effective trade network development. After having slowed down as a consequence of the global economic crisis, the retail sector is experiencing strong expansion in the markets of transitional countries. Insufficient engagement of public policy in planning trade networks can violate market competition. An active government role in carrying out the policy of retail network development in transitional countries is necessary to maintain the level of competition and prevent big market players abusing their dominant position.